Edge effects on the phenology of the guamirim, Myrcia guianensis (Myrtaceae), a cerrado tree, Brazil - Vogado, Nara Oliveira; de Camargo, Maria Gabriela Gutierrez; Locosselli, Giuliano Maselli; Morellato, Leonor Patrícia Cerdeira (Tropical conservation science, 2016)
The Brazilian cerrado, a hotspot of biodiversity, has suffered intense fragmentation in the last decades with an associated increase in areas subjected to edge effects. Plant phenology may be influenced by abiotic changes induced by edge effects, such as increases in temperature and light. We studied the phenology of the guamirim (Myrcia guianensis, Myrtaceae) and its relation to local abiotic factors in a Brazilian cerrado area between 2005 and 2011, aiming to answer: (i) whether M. guianensis phenology differs between the edge and the interior and/or between cardinal orientations at the study site, given that environments facing east are lighter and warmer than environments facing south; and (ii) how microenvironmental factors influence the observed phenological patterns. We sampled 92 individuals in 36 transects (25m × 2m), distributed along the edge and in the interior (100m from the edge) of the east and south faces. Myrcia guianensis presented seasonal patterns of leafing and reproduction, but only reproduction was influenced by microenvironmental conditions. Individuals on the east edge — the warmest and driest environment with the most light — presented with the highest synchrony and intensity of reproductive phenophases, followed by the east interior, south interior and south edge. Flowering and fruiting onset and peak dates occurred around 20 days earlier on the east edge than the south face. Edge conditions, primarily cardinal orientation, and associated higher temperatures and light incidence influenced the reproductive phenology of M. guianensis and the onset of flowering and fruiting. We suggest that edges could be used to evaluate plant responses to the temperature increases predicted for future climate change scenarios.